Knee cap bursitis/housemaid’s knee role of magnetic resonance imaging: A case report - Amandeep Singh,; Aaina Devgan,; Sumanjeet Kaur,; Prabhjot Singh, (Indian Journal of Case Reports, 2021)
Pre-patellar bursitis is one of the major causes of anterior knee pain affecting people between 40 and 60 years of age. It occurs secondary to trauma, infection, overuse, systemic illness, and inflammatory arthropathy. Bursitis can be associated with certain occupations and named accordingly such as pre-patellar bursitis is also known as housemaid knee. Here, we present the case of a 65-year-old female who presented with visible palpable swelling in the pre-patellar region for 6–7 months which was gradual in onset. Magnetic resonance imaging (MRI) reveals well-defined collection in the pre-patellar bursa along with mild joint effusion. MRI is the modality of choice in this case as it shows high signal intensity on T2 W images and low signal intensity on T1-weighted images. Heterogeneity of the signal is altered when hemorrhage, thickened inflamed synovium, calcification, or loose bodies